Placenta in cosmetic products: an analysis from shariah and legal perspective in Malaysia / Raihanah Badrul Hisham, Nur Azira Tukiran and Mohammad Aizat Jamaludin - Badrul Hisham, Raihanah; Tukiran, Nur Azira; Jamaludin, Mohammad Aizat (Universiti Teknologi Mara Cawangan Pulau Pinang, 2024)
Placenta is available in injections, tablets, creams, and dry food products. Sources of placenta used in products can be derived from humans and animals such as sheep, horses, and pigs. The use of placenta starts with the finding of its high nutrient content, which is found to be useful for skin and wound healing for humans. The issue is whether the use of placenta in cosmetic products is permissible or not. Hence, this paper focuses on the status of cosmetic products containing placenta according to Islamic perspectives and laws in Malaysia. The qualitative approach through the method of document analysis was used. The study outcomes reveal uncertainty about the halal status of cosmetic products containing placenta. According to the fatwa, placentas obtained from halal animals and slaughtered accordant to Shariah law could be used for beauty purposes. However, placentas taken from human sources are prohibited to prevent exploitation of the human body. Placenta is not listed as a prohibited ingredient in the Guidelines for Control of Cosmetic Products in Malaysia by the National Pharmaceutical Regulatory Agency (NPRA), the Ministry of Health (MOH). However, the Department of Islamic Development Malaysia (JAKIM) has a different status for placenta products and refuses to issue halal certificates for those products.